Chantiers de reconstruction politique en comparaison : La « décentralisation » en période post-révolutionnaire en Tunisie et en Libye - Sami Yassine Turki; Chiara Loschi (L’Année du Maghreb)
The 2011 Arab uprisings had a strong territorial dimension, highlighting the importance of the territorial aspects of public policies and their failures in terms of equity and development. Thus, decentralization, as a device of institutional re-legitimation, gained a moment of success. In this context, Tunisia and Libya represent two countries that experienced deep regime change after 2011: in both cases, political regimes are so entrenched in institutions that the post-revolutionary reconstruction of the state is supposed to be radical. In these countries, changes towards stability are almost at the opposite, but decentralization has quickly emerged as an essential component of the political system reconfiguring, being a key element of the constitutional change (Tunisia) or preceding it (Libya). The authors propose here to compare the process of decentralization policies building after the fall of the authoritarian regimes, emphasizing the importance of the institutional and political heritage on the one hand, the role of local actors, on the other hand.The comparison of the two countries under the transition, referring to the contrasting political contexts, allows grasping the roles of the old and new actors, the articulation between old and new institutional mechanisms, and the emergence of new practices at the local level. Thus, the question of the state’s response to these processes, through the commitment - or its simulation - to decentralization (Tunisia) and local government (Libya) is problematic.In these countries, the configuration of the municipal authorities during the transition underwent radical differences, whose analysis contributes to the understanding of the legitimation strategies and reconstruction of the states at different scales. In this sense, it is even more promising to analyse how local groups are positioned in the two different contexts, between national institutional reconfiguration, development programs and reorganization of local interests that precede the Revolution.